2010
DOI: 10.1111/j.1744-7402.2009.02449.x
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Characterization of High‐Performance C/SiC‐Ceramics Using X‐Ray‐Computed Tomography

Abstract: The quality control of ceramic matrix composites (CMC) has always been a challenge due to their anisotropy and inhomogeneity. Using high‐resolution X‐ray computed tomography, these materials can be analyzed in situ during the manufacturing process, providing a three‐dimensional analysis without damaging or modifying the samples. This paper analyzes the three material states CFRP, C/C and C/SiC that occur during the processing of melt‐infiltrated C/SiC composites and describes the changes in morphology occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Very few such studies have been made of C/C-SiC composites. For instance, Hausherr et al [33] used high-resolution XCT to observe the morphology changes in C/C and C/SiC with each LSI processing step, and some of the authors of this work have previously demonstrated the application of combined XCT/DVC in a study of compressive damage development within a 3D braided C/C-SiC composite, fabricated by GSI [13].…”
Section: Introductionmentioning
confidence: 99%
“…Very few such studies have been made of C/C-SiC composites. For instance, Hausherr et al [33] used high-resolution XCT to observe the morphology changes in C/C and C/SiC with each LSI processing step, and some of the authors of this work have previously demonstrated the application of combined XCT/DVC in a study of compressive damage development within a 3D braided C/C-SiC composite, fabricated by GSI [13].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, identical volumes and cross-sections were determined and examined. 31) The effect of shrinkage can be clearly seen in the shown example of the two-dimensional cross-sections. The diameter decreases form initially 10.4 mm in the cross-linked, precreamic state, to 7.7 mm after pyrolysis.…”
Section: Micro Computed Tomography Measurementsmentioning
confidence: 88%
“…29), 30) Modern X-ray micro-computed tomography (¯-CT) permits the three-dimensional visualization of samples with resolutions less than ³5 microns. 31) For a CT-analysis, the sample is positioned between an X-ray source and a detector; the basic information of the analyzed specimen is based on the X-ray attenuation. The sample is rotated in small increments to acquire multiple radioscopic images (up to 2000 images) from different positions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, XCT as an advanced non-destructive technique has been applied to a wide range of materials, including wood [13], concrete [14], gypsum [15], graphite [16,17] and polymer composites [18]. Various ceramic matrix composites [19][20][21][22][23] have also been investigated, but only a few studies have examined C/C-SiC composites [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%